Dissecting Morphological and Functional Dynamics of Non‐Tumorigenic and Triple‐Negative Breast Cancer Cell Lines Using PCA and t‐SNE Analysis - Yazan A. Almahdi; Eva R. Schwark; Aidan J. Mclaughlin; Besa Xhabija (Cancer Reports, 2025)
ABSTRACT Background Triple‐negative breast cancer (TNBC) poses significant challenges due to its aggressive nature and lack of targeted therapies. Understanding the cellular behaviors of TNBC is crucial for developing effective treatments. Aims This study aims to compare the morphological characteristics of non‐tumorigenic MCF10A and aggressive MDA‐MB‐231 TNBC cell lines using advanced analytical techniques. Methods and Results Advanced techniques such as Principal Component Analysis (PCA), t‐Distributed Stochastic Neighbor Embedding (t‐SNE), and digital holographic microscopy were utilized. Cellular features such as area, migration, motility, irregularity, and optical thickness were thoroughly analyzed over time. Our results revealed significant morphological differences between the MCF10A and MDA‐MB‐231 cell lines. Specifically, MDA‐MB‐231 cells displayed enhanced motility and a smaller, more variable size, attributes that may facilitate their invasive potential. In contrast, MCF10A cells exhibited larger sizes and more regular migration patterns, suggesting stability in structured tissue environments. Additionally, temporal analysis highlighted consistent phenotypic behaviors over time, with MDA‐MB‐231 cells demonstrating higher optical thickness and irregularity, indicating potential structural complexities associated with malignant transformation. Correlative analysis further confirmed these results by revealing connections between cell size, motility, and optical properties crucial for understanding cell behavior within their microenvironment. Conclusion The profound differences in cellular dynamics between MCF10A and MDA‐MB‐231 cell lines underscore the unique adaptive mechanisms of TNBC cells. Our study provides valuable insights into the cellular foundations of TNBC aggressiveness, offering a foundation for future research aimed at understanding the mechanistic underpinnings of TNBC progression and therapeutic targeting.